A Retrospective Study on Postoperative Complications in Gynecological Surgeries: Identification of High-Risk Factors and Best Practices - Kshirsagar, Shilpa; Jagdale, Supriya; Datar, Meghana; Bhagat, Shyam (International Journal of Statistics in Medical Research, 2025)
Background: Laparoscopic gynecologic surgery is widely favored for its minimally invasive nature, offering reduced postoperative pain, shorter hospital stays, and faster recovery. However, despite its advantages, postoperative complications—ranging from minor infections to major injuries—remain a concern. Identifying patient- and procedure-specific risk factors is critical to enhancing surgical safety and outcomes. Objective: To evaluate the incidence and predictors of postoperative complications in gynecologic laparoscopic surgeries and identify high-risk patient and procedural factors using a large, retrospective dataset. Methods: This retrospective cohort study included 15,308 patients who underwent laparoscopic gynecologic procedures at tertiary care hospitals in Pune, India, between January 2023 and October 2024. Patients were categorized by procedure type: adnexal surgery, myomectomy/uterine lesion surgery, LAVH/TLH, and malignancy surgery. Data on demographics, prior surgical history, comorbidities, and surgical details were collected. Complications were classified as major (e.g., bowel or ureteral injury, hemorrhage requiring reoperation) or minor (e.g., infection, transient fever). Multivariate logistic regression identified independent risk factors for major complications. Results: The overall major complication rate was 0.51%, and the minor complication rate was 4.64%. Surgeries for malignancy had the highest major complication rate. Independent risk factors for major complications included age 31–60 years (aOR: 2.88; 95% CI: 1.89–7.88), age >60 years (aOR: 2.92; 95% CI: 1.67–5.65), prior abdominal surgery (aOR: 3.58; 95% CI: 1.38–6.54), obesity (aOR: 2.52; 95% CI: 1.39–7.28), and higher surgical complexity (e.g., malignancy surgery vs. adnexal: aOR: 7.62; 95% CI: 3.61–13.63). Conclusion: Although complication rates in laparoscopic gynecologic surgery remain low, advanced age, obesity, previous abdominal surgery, and complex procedures significantly increase the risk of major complications. These findings underscore the need for thorough preoperative assessment, individualized surgical planning, and targeted risk mitigation strategies to optimize patient outcomes.